Research Progress on Cell Membrane-Coated Biomimetic Delivery Systems - Guo, Mengyu; Xia, Chenjie; Wu, Yu; Zhou, Nong; Chen, Zhipeng; Li, Weidong (Frontiers in Bioengineering and Biotechnology, 2021)
Cell membrane-coated biomimetic nanoplatforms have many inherent properties, such as bio-interfacing abilities, self-identification, and signal transduction, which enable the biomimetic delivery system to escape immune clearance and opsonization. This can also maximize the drug delivery efficiency of synthetic nanoparticles (NPs) and functional cell membranes. As a new type of delivery system, cell membrane-coated biomimetic delivery systems have broadened the prospects for biomedical applications. In this review, we summarize research progress on cell membrane biomimetic technology from three aspects, including sources of membrane, modifications, and applications, then analyze their limitations and propose future research directions.